INSTAGRAM AS MEDIA IN TEACHING WRITING RECOUNT TEXT FOR SENIOR HIGH SCHOOL STUDENTS - Abdul Basith; Ahmad Syafi’i (SALEE, 2020)
Social media is web-based application that allows users to communicate, collaborate, and share resources with other people. Both being easy to access and easy to use make social media become an effective way to communicate and exchange ideas. Students can use social media to keep up with their friends, to stay up-to-date with news and current events, to fill up spare time, to find entertaining content, and to share opinions. The use of social media becomes famous for the students nowadays. Thus, the popularity of the social media among students can be used as a tool in language teaching. One of the famous social media is Instagram. Instagram is a social network that enables its users to take pictures and videos, and share them publicly or privately on the application, as well as through a variety of other social network. Through Instagram the students can post their photos or videos that can be commented by viewers. By using Instagram, teachers are offered great opportunity to develop classroom activities creatively. This paper will give an overview of the use of Instagram in teaching writing recount text in senior high school students.